1982
DOI: 10.1016/s0022-5347(17)53725-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Parameters in Superficial Bladder Cancer: An Analysis of 315 Cases

Abstract: A retrospective study of 315 patients with superficial transitional cell carcinoma (stages Ta to T2) and an adequate followup of 3 years or longer is reported. Transurethral resection was done in 80 per cent of the patients and open excision or resection was done in 20 per cent for cure or control. We herein demonstrate that, in addition to grade and stage, multifocal tumor growth and whether the tumor is primary or recurrent influence the frequency of recurrences and tumor progression. The over-all recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
145
1
18

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(167 citation statements)
references
References 10 publications
3
145
1
18
Order By: Relevance
“…3,85 Tumor Multifocality Development of multifocal tumors in the same patient, either synchronous or metachronous, is a common characteristic of urothelial malignancy. [132][133][134][135] Premalignant changes, such as dysplasia or CIS, often are found in urothelial mucosa aside from an invasive bladder cancer. 136,137 Studies of urothelial genetic alterations and atypia mapping in cystectomy specimens confirm the importance of field cancerization in the development of multifocal urothelial tumors, especially in early stage cancer.…”
Section: Tumor Sizementioning
confidence: 99%
See 1 more Smart Citation
“…3,85 Tumor Multifocality Development of multifocal tumors in the same patient, either synchronous or metachronous, is a common characteristic of urothelial malignancy. [132][133][134][135] Premalignant changes, such as dysplasia or CIS, often are found in urothelial mucosa aside from an invasive bladder cancer. 136,137 Studies of urothelial genetic alterations and atypia mapping in cystectomy specimens confirm the importance of field cancerization in the development of multifocal urothelial tumors, especially in early stage cancer.…”
Section: Tumor Sizementioning
confidence: 99%
“…Some studies have suggested that tumor multifocality Staging and reporting of bladder cancer L Cheng et al is associated with poor outcome for patients with urothelial carcinoma. 130,134,135,142 Cohorts in these studies were limited to early stage (Ta and T1) bladder cancer. In a recent study of cystectomy specimens, which included more advanced cancers, tumor multifocality did not have prognostic significance.…”
Section: Tumor Sizementioning
confidence: 99%
“…[1][2][3][4][5] Despite advances in radical surgery or adjuvant chemotherapy, the 5-year survival rate for patients with invasive cancer is still about 50%. 6 Because telomerase is detected in more than 90% of bladder cancer, but not in normal bladder tissues, 12,13 we expect that 2-5A-anti-hTR is a promising therapeutic agent for the treatment of bladder cancer.…”
Section: Oligonucleotide Mixed With Lipofectamine (4 L/ml) Every 24mentioning
confidence: 99%
“…2,3 However, 15% of these tumors progress to muscle-invasive cancer and required cystectomy. 4,5 In contrast with superficial tumors, the prognosis of advanced bladder cancer is poor and the 5-year survival rate is about 50% even after the radical surgical excision. 6 Therefore, in order to improve prognosis of bladder cancer, it is absolutely essential to explore a novel modality of treatment.…”
mentioning
confidence: 99%
“…Over 75% of patients present with one or more superficial tumours, and two thirds of these will develop recurrent disease (Lutzeyer et al, 1982), with 10 -20% progressing to an invasive phenotype (Torti and Lum, 1984). The outcome for patients with invasive disease at presentation remains poor, with distant metastasis occurring in over 50% within 2 years and an average 5-year survival of only 50% (Raghavan et al, 1990).…”
mentioning
confidence: 99%